OPTIMALISASI LAHAN KERING KECAMATAN BAYAN-LOMBOK UTARA MENGGUNAKAN ASAM HUMAT TERIMMOBIL DALAM RUMPUT LAUT SEBAGAI PELENGKAP PUPUK PADA TANAMAN JAGUNG (Zea Mays L) - Dhony Hermanto; Siti Raudhatul Kamali; Rina Kurnianingsih; Nurul Ismillayli (Faculty of Agriculture, Universitas Sebelas Maret, 2013)
Title : The Optimization of Bayan District Dry Land –North Lombok Used The Immobilized Humic Acid in Seaweed as Fertilizer Supplement for Maize Plant (Zea Mays L). A study on optimization of dry land used the immobilized humic acid in seaweed as fertilizer supplement for maize plant (Zea Mays L) has been done in Bayan District North Lombok Regency Nusa Tenggara Barat Province. It was known that humic acid could increase availability and uptake of nutrient (N, P, K and Corganic) at maize plant in dry land of Bayan District. It was needed a modification technique that lower quantity of humic acid using without diminishing it’s utility, by immobilized humic acid in seaweed. Research design began with the preparation of immobilized humic acid in seaweed via entrapment technique (gel) and covalent bending (liquid). Immobilization result was characterized by infrared spectrophotometer. Agircultural land was mapped according to number of treatments, then each of them was analized physical and chemical properties before planting was done. Bayan agricultural land has sandy and loose texture, reddish brown colour, and neutral acidity (pH 6.97 at depth of 0-20 cm and a pH of 6.80 at depth of 21-40 cm). It has low availability nutrient of soil (Corganic, N, P, K) at 0-20 cm depth and 21-40 cm respectively are 2.950% and 2.860%, 0.067% and 0.076%, 0.001% and 0.004 %, 0.310% and 0.390%. While the cation exchange capacity value at a depth of 0-20 cm and 21-40 cm respectively are 20.95 and 22.16 me. Based on FTIR spectra, humic acid can be immobilized on seaweed as evidenced by absorption shift, especially in the carboxylic acid and amine groups. Humic acid was able to increase nutrient availability and uptake at maize plant through it’s ability in binding, adsorbing and exchanging nutrients. Application of humic acid in soil showed increasing of plant growth (plant height, weight and nutritional value of corn). Availability and uptake of N, P and K are highest in treatment 0.1% humic acid immobilized on seaweed 100 kg ha-1 (gel) and 0.1% humic acid immobilized in seaweed (liquid) with fertilizer 100% NPK dose.